Long-term Efficacy of Orthokeratology Contact Lens Wear in Controlling the Progression of Childhood Myopia - Santodomingo-Rubido, Jacinto; Villa-Collar, César; Gilmartin, Bernard; Gutiérrez-Ortega, Ramón; Sugimoto, Keiji (Current eye research, 2017)
Purpose: The primary outcome of this study is to compare the axial length growth of white European myopic children wearing orthokeratology contact lenses (OK) to a control group (CT) over a 7-year period. Methods: Subjects 6-12 years of age with myopia −0.75 to −4.00DS and astigmatism ≤1.00DC were prospectively allocated OK or distance single-vision spectacles (SV) correction. Measurements of axial length (Zeiss IOLMaster), corneal topography, and cycloplegic refraction were taken at 6-month intervals over a 2-year period. Subjects were invited to return to the clinic approximately 5 years later (i.e., 7 years after the beginning of the study) for assessment of their ocular refractive and biometric components. The CT consisted of 4 SV and 12 subjects who switched from SV to soft contact lens wear after the initial 2 years of SV lens wear. Changes in axial length relative to baseline over a 7-year period were compared between groups. Results: Fourteen and 16 subjects from the OK and CT groups, respectively, were examined 6.7 ± 0.5 years after the beginning of the study. Statistically significant changes in the axial length were found over time and between groups (both p < 0.001), but not for the time*group interaction (p = 0.125). The change in the axial length for the OK group was 22% (p = 0.328), 42% (p = 0.007), 40% (p = 0.020), 41% (p = 0.013), and 33% (p = 0.062) lower than the CT group following 6, 12, 18, 24, and 84 months of lens wear, respectively. Conclusion: A trend toward a reduction in the rate of axial elongation of the order of 33% was found in the OK group in comparison to the CT group following 7 years of lens wear.